Use of the Computadorized Local Anesthesia System The Wand in Pediatric Dentistry - Italo Medeiros FARACO JUNIOR; Ana Letícia Rower DABLE; Andréia Bertani OTTONI; Marcela MARQUEZAN; Maximiano Ferreira TOVO; Paulo Floriani KRAMER (Association of Support to Oral Health Research (APESB), 2007)
Introduction: The positive behavior of pediatric patients depends, among others variables, on the success of local anesthesia. Objective: In sight of this, we carried out a review about anesthesic techniques using the computerized anesthesia. This system has as main objective to reduce the discomfort caused by the traditional anesthesia, by controlling two important factors for the success of the local anesthesia: the pressure and the volume of anesthesic. Conclusion: The majority of the revised papers demonstrated that The Wand System is superior to the traditional anesthesia, when modified techniques are used.